PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Persepsi pada Karyawan Kantor Pusat PT. TASPEN (PERSERO) ) - Nuryono Haryadi, - (2020)
This research is motivated by the gap between generations at the Head Office of PT. TASPEN (PERSERO), where the gap between generations raises human resource problems for the company, such as the low Organizational Citizenship Behavior employees at the Head Office of PT. TASPEN (PERSERO), therefore this research will focused on Organizational Citizenship Behavior. And identify the background of this problem, researchers assumed that Organizational Culture can be a solution to overcome this problem. The purpose of this study was to determine the description of Organizational Culture and Organizational Citizenship Behavior at the Head Office of PT. TASPEN (PERSERO) and also to determine the effect of Organizational Culture on Organizational Citizenship Behavior at the Head Office of PT. TASPEN (PERSERO). This research used descriptive verification method with a population of 435 employees and a samples of 81 employees of the Head Office of PT. TASPEN (PERSERO), by using a propotionate stratified random sampling technique. The analysis technique used Pearson product moment correlation coefficient and simple regression analysis. Hypothesis testing uses t-test to see the effect partially. The results of this study indicate that the Organizational Culture of PT. TASPEN (PERSERO) is in the medium category and Organizational Citizenship Behavior is in the high category. And from the relationship between these two variables, the correlation coefficient value obtained is 0.641 with a significance level of 0.000 and a determination coefficient of 41.1%, this shows that Organizational Culture has a positive and significant effect on Organizational Citizenship Behavior. Keywords: Organizational Culture, Organizational Citizenship Behavior